Groundhog's dilemma - Remenar, Kristen,Faulkner, Matt (Charlesbridge, 2015)
Groundhog wants to please all the animals, but half of them want spring to come quickly and the other half do not...and all of them think he controls the seasons, so what is a poor groundhog to do on Groundhog Day?
Keywords: Bilderbuch; Kinderbuch; Woodchuck; Animals; Groundhog Day; Spring; Ethical problems; Friendship; Forest animals; Seasons; Conduct of life